Segment-Based Adaptive Landscape Design for Riparian Restoration of the Amprong River - Dimas Wahyu Pratama; Irawan Setyabudi; Mochammad Azkari Hisbulloh Akbar (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2026)
The Riparian zone of the Amprong River in the Upper Brantas Sub-watershed, Malang City, has undergone ecological degradation due to land conversion, informal settlements, and domestic waste pollution. This study aims to assess riparian conditions and develop an adaptive landscape design strategy for ecological restoration. A descriptive–spatial case study approach was employed, integrating field observation, vegetation surveys across five purposively selected segments, photographic documentation, and spatial analysis using ArcGIS. The results reveal high ecological vulnerability in segments characterized by steep slopes, low vegetation cover, and building distances of less than 10 meters from the riverbank. The proposed design emphasizes a layered ecological zoning strategy incorporating native and pioneer species such as Gigantochloa apus, Swietenia macrophylla, and Imperata cylindrica to enhance hydrological buffering capacity and restore habitat connectivity. This study proposes a segment-based adaptive ecological zoning model that links site-specific vulnerability with targeted design interventions, offering a practical framework for restoring degraded urban riparian systems.